The secretome of alginate-encapsulated limbal epithelial stem cells modulates corneal epithelial cell proliferation. - Bernice Wright; Andrew Hopkinson; Martin Leyland; Che J Connon (PLoS ONE)
Limbal epithelial stem cells may ameliorate limbal stem cell deficiency through secretion of therapeutic proteins, delivered to the cornea in a controlled manner using hydrogels. In the present study the secretome of alginate-encapsulated limbal epithelial stem cells is investigated. Conditioned medium was generated from limbal epithelial stem cells encapsulated in 1.2% (w/v) calcium alginate gels. Conditioned medium proteins separated by 1-D gel electrophoresis were visualized by silver staining. Proteins of interest including secreted protein acidic and rich in cysteine, profilin-1, and galectin-1 were identified by immunoblotting. The effect of conditioned medium (from alginate-encapsulated limbal epithelial stem cells) on corneal epithelial cell proliferation was quantified and shown to significantly inhibit (P≤0.05) their growth. As secreted protein acidic and rich in cysteine was previously reported to attenuate proliferation of epithelial cells, this protein may be responsible, at least in part, for inhibition of corneal epithelial cell proliferation. We conclude that limbal epithelial stem cells encapsulated in alginate gels may regulate corneal epithelialisation through secretion of inhibitory proteins.